Torsion of a Large Appendix Testis Misdiagnosed as Pyocele - Susanta Meher; Satyajit Rath; Rakesh Sharma; Prakash Kumar Sasmal; Tushar Subhadarshan Mishra (Case Reports in Urology)
Torsion of the appendix testis is not an uncommon cause of acute hemiscrotum. It is frequently misdiagnosed as acute epididymitis, orchitis, or torsion of testis. Though conservative management is the treatment of choice for this condition, prompt surgical intervention is warranted when testicular torsion is suspected. We report a case of torsion of a large appendix testis misdiagnosed as pyocele. Emergency exploration of it revealed a large appendix testis with torsion and early features of gangrene. After excision of the appendix testis, the wound was closed with an open drain. The patient had an uneventful and smooth postoperative recovery.